Peroxiredoxin 1 Promotes Proinflammatory Cytokine Secretion in Human Dysplastic Oral Keratinocytes and Mouse Tongue Precancerous Tissues - Min Zhang; Wenjing Li; Jing Li; Wenchao Wang; Lingyu Li; Yunping Lu; Min Wang; Xiaofei Tang (Analytical Cellular Pathology)
Oxidative stress, a widespread phenomenon involved in many pathological conditions, may be closely related with the progression of oral leukoplakia (OLK). Under chronic inflammation, oxidative stress could stimulate the local formation of a tumor-specific microenvironment in some types of cancer, though not well defined in oral cancer even in OLK. Peroxiredoxin 1 (Prx1), a widely expressed sulfhydryl antioxidant protein, is overexpressed in various tumors and affects tumorigenesis, cell proliferation, apoptosis, invasion, and metastasis. Prx1 also acts as a potent proinflammatory factor. Nuclear factor (NF)-κB is a member of the core dimeric transcription factor family that coordinates the inflammatory response. To investigate the role of Prx1 in oxidative stress-related inflammation in OLK, a coculture model of human dysplastic oral keratinocyte (DOK) and human epidermal fibroblast (HFF) was established and stimulated with H2O2. Cellular reactive oxygen species (ROS) and Prx1 levels in DOK were determined via flow cytometry and western blotting, respectively. Additionally, the levels of the inflammatory factors, interleukin (IL)-6, IL-8, IL-10, and interferon (IFN)-γ, in the conditioned medium were determined via enzyme-linked immunosorbent assay (ELISA). DOK nuclear expression of NF-κB was detected via immunofluorescence assay and western blotting. Moreover, the expression levels of inflammatory factors and the nuclear expression of NF-κB were examined in 4-nitroquinoline-1-oxide (4NQO)-induced tongue precancerous tissues of mice. H2O2 increased Prx1 levels and nuclear expression levels of NF-κB in DOKs and mouse tongue precancerous tissues and elevated the levels of IL-6, IL-8, IL-10, and IFN-γ secreted in the culture supernatants and mouse tongue tissues. However, Prx1 knockdown in DOK and mouse tongue tissues attenuated the upregulation of inflammatory factor and nuclear NF-κB expression levels. Overall, our results suggest that oxidative stress increases Prx1 expression, which promotes inflammatory factor expression by activating NF-κB in human DOK and mouse tongue precancerous tissues.